2014
DOI: 10.1242/dmm.014076
|View full text |Cite
|
Sign up to set email alerts
|

A tissue-engineered humanized xenograft model of human breast cancer metastasis to bone

Abstract: The skeleton is a preferred homing site for breast cancer metastasis. To date, treatment options for patients with bone metastases are mostly palliative and the disease is still incurable. Indeed, key mechanisms involved in breast cancer osteotropism are still only partially understood due to the lack of suitable animal models to mimic metastasis of human tumor cells to a human bone microenvironment. In the presented study, we investigate the use of a human tissue-engineered bone construct to develop a humaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 59 publications
2
98
0
Order By: Relevance
“…Our group has already demonstrated that melt electrospun PCL scaffolds are suitable to engineer bone constructs to study species-specific mechanisms in vivo [24,25]. However, the endosteallike ECM deposition by hOBs on melt electrospun PCL scaffolds has not been characterised [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has already demonstrated that melt electrospun PCL scaffolds are suitable to engineer bone constructs to study species-specific mechanisms in vivo [24,25]. However, the endosteallike ECM deposition by hOBs on melt electrospun PCL scaffolds has not been characterised [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Melt electrospun written scaffolds made of medical grade poly(ɛ-caprolactone) (PCL) have supported de novo formation of bone in vivo [24,25]. Thus, melt electrospun PCL scaffolds represent a 3D testing platform to tailor characteristic components of the endosteal niche in a highly controlled fashion.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the role of BMPR1a in tumor-stromal interaction in bone metastasis, human breast cancer MDA-MB-231-luc cells were injected intratibially into nude mice to construct a breast cancer bone metastasis model [23]. Immunofluorescent analysis for BMPR1a of tumor-bearing bone sections obtained from different metastatic mice demonstrated a stronger staining of BMPR1a of breast cancer cells at the tumor-bone interface, compared with cancer cells distant from the interface (Fig.…”
Section: Bmpr1a Is Prominently Expressed In Metastatic Breast Cancer mentioning
confidence: 99%
“…We and others have described the development of large volume bone implants with a physiologically relevant morphology and which include a high number of human stromal cells. 5,6 Different research groups utilize hBMSCs to engineer ectopic humanized bone tissues. However, most of them do not demonstrate the retention of the human cells after transplantation, nor do they characterize the degree of humanization of the newly formed tissue.…”
mentioning
confidence: 99%
“…Another key aspect which is largely missing in most studies is evidence not only of the presence of human cells in the engineered tissues but also of the incorporation of humanderived extracellular matrix (ECM). 6 In fact the bone niche regulates the behavior of normal and malignant cells via various chemo-attractive and adhesive pathways, which include cell-cell as well as cell-ECM interactions. In our recently published paper we have shown that the b1 integrin cell-ECM adhesion molecules expressed by breast cancer cells play a significant role in the development of metastases within a humanized bone microenvironment.…”
mentioning
confidence: 99%